EduHealth Time Application for Enhancing Nutrition and Health Knowledge and Skills among Junior High School Students - Nugroho, Fajar Ari; Kusumastuty, Inggita; Cempaka, Anggun Rindang (Universitas Ahmad Dahlan, 2025)
Background: Adolescents often acquire health knowledge through traditional education but frequently face challenges in sustaining healthy behaviors due to a range of social, environmental, psychological, and developmental factors. Contribution: We developed